Efeitos de exercícios supervisionados versus minimamente supervisionados na incapacidade, dor e qualidade de vida de indivíduos jovens com dor cervical crônica não específica: ensaio clínico randomizado - Castro, Pedro Henrique Martins de (2024)
Objective: purpose of this study was to investigate the non-inferiority of a minimally supervised versus supervised exercise program (with equal doses of training) over 8 weeks, on neck disability, pain intensity and and quality of life of individuals with chronic nonspecific neck pain (CNSNP). Design: single-center, non-inferiority randomized controlled trial, two-arm, parallelgroup. Setting: The study was conducted at the Federal University of Rio Grande do Norte, RN, Brazil. Participants: 76 participants of both sexes, with CNSNP. Intervention: Subjects will be randomized into two groups: supervised exercise e minimally exercise group. Both groups will perform an eight-week program (twice a week) with range of motion and motor control exercises for the cervical spine. Measurements: The primary outcome will be neck disability. Secondary outcomes included pain intensity, pressure pain threshold, strength, neuromo tor control, range of motion, quality of life, kinesiophobia, catastrophizing, and selfefficacy. All outcomes were assessed before and after the exercise program. The Global Perceived Effect was used to evaluate perceived improvement. Results: Both groups (A and B) showed improvements in pain intensity, with no statistically significant difference between them. Additionally, there was no significant difference in most secondary outcomes, except for quality of life, kinesiophobia, and pain self-efficacy, where group A showed better results. The pressure pain threshold was better in group B. Conclusions: Minimally supervised exercise groups were non-inferior to supervised exercise for improving neck disability, pain, and quality of life in individuals with mild to moderate CNSNP in a physically active young adult population. Trial registration: RBR-8bbz36g.